(untitled) (Forum Penelitian Agro Ekonomi, 2020)
The new paradigm of agricultural development placed Agricultural-Demand-Led-Industrialization (ADLI) strategy as an industrialization strategy emphasizing agriculture development program and setting the agriculture sector as a prime mover of industry and other sectors. The strategy is considered appropriate to be applied in developing countries which agriculture sector is their main resource. This paper aims to analyze the role of ADLI strategy in developing countries, including Indonesia, on macroeconomic performance and on farmers and land less households’ income improvement. The main result of this study is that ADLI strategy has an important role on macroeconomic performance, especially on labor absorption, GDP improvement as well as on other sector’s income acceleration. However, the strategy is quite a distance from an ideal implementation in terms of household income distribution. The benefit gained from agriculture and agroindustry sector development was mostly pour to non agriculture households in urban areas while farmer’s households and especially those of landless gained the least.